2020
DOI: 10.3390/pharmaceutics12090823
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Validation of Spray-Dried Mesoporous Bioactive Glass Microspheres Acting as Prolonged Local Release Systems for BMP-2 to Support Bone Regeneration

Abstract: Bone morphogenetic protein-2 (BMP-2) is a known key mediator of physiological bone regeneration and is clinically approved for selected musculoskeletal interventions. Yet, broad usage of this growth factor is impeded due to side effects that are majorly evoked by high dosages and burst release kinetics. In this study, mesoporous bioactive glass microspheres (MBGs), produced by an aerosol-assisted spray-drying scalable process, were loaded with BMP-2 resulting in prolonged, low-dose BMP-2 release without affect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…In the present study, low levels of loading were recorded because of the low amount of protein that was added in relation to MSN weight (1 μg of protein per 2.81 mg of MSNs). In other studies using spray-dried mesoporous bioactive glass microspheres [ 41 ] or pure mesoporous silicate nanoparticles [ 42 ], the protein amount was significantly higher in relation to MSN mass, thus yielding higher loading capacity. However, the exact dose of rhBMP-2 that can promote bone regeneration in different clinical applications without adverse effects has yet to be discovered, as different studies have reported controversial findings [ 43 , 44 , 45 ], increasing the reluctance and insecurity of clinicians to apply it [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, low levels of loading were recorded because of the low amount of protein that was added in relation to MSN weight (1 μg of protein per 2.81 mg of MSNs). In other studies using spray-dried mesoporous bioactive glass microspheres [ 41 ] or pure mesoporous silicate nanoparticles [ 42 ], the protein amount was significantly higher in relation to MSN mass, thus yielding higher loading capacity. However, the exact dose of rhBMP-2 that can promote bone regeneration in different clinical applications without adverse effects has yet to be discovered, as different studies have reported controversial findings [ 43 , 44 , 45 ], increasing the reluctance and insecurity of clinicians to apply it [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In certain clinical situations, MBGs or MBG-based materials do not make direct contact with cells, however, their dissolution products or leachates could reach targeted cells; this could explain the significant use of extraction techniques (indirect cultivation setting) when assessing cytocompatibility of materials [ 21 , 55 , 59 , 81 , 91 , 95 , 100 , 101 ]. In a test based on direct contact, the material sample is in physical contact with the cells; this system also has some clinical relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Most recent research has administered rhBMP-2 protein directly into the culture medium or intravenously, which may cause stress conditions for cells and tissues. The advantages of a sustained, low-dose release of BMP-2, including less inflammation and ectopic ossification, have been verified ( Wildemann et al, 2004 ; Ji et al, 2010 ; Seo et al, 2017 ; Berkmann et al, 2020 ; Xin et al, 2020 ). The mitigatory inflammatory surroundings can reduce the risk of tumorigenesis as well, which makes low-dose BMP-2 application more reasonable.…”
Section: Reasons For Contradictory Conclusionmentioning
confidence: 97%
“…However, these 2D models hardly mimic tumor cell biology because of tumor heterogeneity and different responses to secreted cytokines, growth factors, and methylation states of the cells. Moreover, the 2D cell culture systems cannot sufficiently simulate a three-dimensional (3D) physiological microenvironment, so they fail to provide physiologically relevant information regarding cell–cell interactions, cell–extracellular matrix interactions, growth factor synthesis, or physical and chemical cues to oncogenesis ( Hickman et al, 2014 ; Berkmann et al, 2020 ). Furthermore, the results obtained from gene expression analysis and drug resistance also differ substantially between 2D and 3D cell culture models ( Zhao et al, 2014 ; Costa et al, 2016 ; Henriksson et al, 2017 ; Zhou et al, 2017 ; Fontoura et al, 2020 ; Mao et al, 2020 ; Sun et al, 2020 ; Xie et al, 2021 ).…”
Section: Limitations In Present Studiesmentioning
confidence: 99%